Annexin A4 N‐terminal peptide inhibits adenylyl cyclase 5 and limits β‐adrenoceptor‐mediated prolongation of cardiac action potential. Issue 8 (24th June 2020) - Heinick, Alexander; Pluteanu, Florentina; Hermes, Christina; Klemme, Andre; Domnik, Manuel; Husser, Xenia; Gerke, Volker; Schmitz, Wilhelm; Müller, Frank U.
Abstract: Adenylyl cyclases (AC) are essential for the normal and pathophysiological response of many cells. In cardiomyocytes, the predominant AC isoforms are AC5 and AC6. Specific AC5 inhibition was suggested as an option for the treatment of heart failure potentially advantageous over β‐blockers. We previously reported an interaction between the calcium‐binding protein annexin A4 (ANXA4) and AC5 in human embryonic kidney 293 (HEK293) cells and an inhibition of cyclic adenosine monophosphate (cAMP) production in cardiomyocytes. Here, we investigated whether ANXA4 is able to differentiate between AC5 and AC6. In transfected HEK293 cells, ANXA4 specifically co‐immunoprecipitated with AC5 and not with AC6, via its N‐terminal domain. Both ANXA4 and a peptide comprising the ANXA4 N‐terminal sequence (A4N1‐22 ) decreased the cAMP production in AC5 and not in AC6 expressing cells. In line with ACs inhibition, in myocytes from ANXA4‐deficient mice, β‐adrenoceptor (βAR) stimulation led to a higher increase of the L‐type calcium current (ICaL ) and to an excessive action potential duration (APD) prolongation as compared to wild‐type cardiomyocytes. This enhanced response was reversed in the presence of A4N1‐22 peptide likely via specific AC5 inhibition. We conclude that via the N‐terminal domain ANXA4 inhibits AC5 not AC6, and that A4N1‐22 as a specific AC5 inhibitor could serve as a novel therapeutic tool for the treatment of AC5‐linked diseases.